Physician Health Literacy Competencies: A Qualitative Study Using Focus Groups - Chia-Chen Chang PhD; Hsiang-Ru Lai; Pei-Ling Tseng PhD; Chun-Cheng Liu PhD; Jin-Lain Ming PhD; Chen-Yin Tung PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Health literacy is crucial for effective physician-patient communication, shared decision-making, and adherence to medical recommendations. This study aims to identify health literacy competencies required for physicians based on insights from physicians, medical interns, and patients. This qualitative study explored physicians’ health literacy competencies through focus group discussions with 21 physicians, medical interns, and patients in Taiwan. Data were analyzed using content analysis to identify key themes and competency domains. Four key physician health literacy competency domains were identified: (1) assessing patients’ health literacy, (2) strengthening physician-patient relationships, (3) facilitating shared decision-making, and (4) Teach-Back and confirmation of patient adherence. These findings highlight essential physician competencies in health literacy, emphasizing the importance of communication, trust, patient-centered decision-making, and structured feedback mechanisms to improve healthcare interactions and outcomes. Strengthening physician’s health literacy competency is essential for improving patient engagement and adherence. Integrating health literacy training into medical education and promoting patient-centered communication can enhance healthcare outcomes.